The University of a Thousand and One Nights - Porter, Luis (Education Policy Analysis Archives, 2005)
This article uses the title of the famous book Arabian Nights which in Spanish (Las mil y una noches) has a time connotation, similar to "for ever and a day" in English. In Spanish, "thousand" is a way to mean "infinite"; if you add one to infinite then you have numberless nights. The article departs from a hypothetical question an academic asks him/herself in his way to the educational institution where he-she works: What is my university? What makes me change from enthusiasm to deception, from pain to happiness? The answers give place to a personal dialogue, which brings the awareness that education overflows from the windows and doors of the classroom, to reach those distant places that Juvenal defined as "ultra Auroram et Gangem" (beyond the rising sun and the Ganges), and that Latin Americans could translate to "beyond the Trópico and the Amazonas." In short, to reach the consciousness that our educational work comprehends a larger territory than the one constrained to the limited geography of a site or an institution. In this broad realm, there are diverse attributes we have to create or recreate: hope, opportunity, imagination, and therefore be able to exercise our capacity to relate, to refer, to reflect. In doing so, we organize, devise, transfer, building our narrative, our capability to plot in each journey a new plan. Every plan is a necessary new story, as those of Sherezade, needed to keep acting day by day, using the word as the only thread that gives meaning to our condition as educators, to our academic being.